Profil Kedisiplinan Siswa Kelas XI SMA Mathla’ul Anwar Menes Tahun Pelajaran 2023/2024 - Muhammad Dirham Nugraha; Vasco Delano; Devi Nurul Fikriyani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Student discipline is very important for students, the definition of student discipline is an orderly and regular state possessed by students at school, without any violations that are detrimental either directly or indirectly to the students themselves and to the school as a whole. Disciplinary violations that occur at school are the responsibility of the principal, homeroom teacher, other teachers and also the BK teacher who is the place to help and guide students to solve any problems that exist in the individual. The purpose of the study was to obtain a profile of the discipline of Class XI students of SMA Mathla'ul Anwar Menes in the 2023/2024 Academic Year. This type of research is quantitative using a descriptive observational research design. The population in this study were all class XI students of SMA Mathla'ul Anwar Menes in the 2023/2024 Academic Year totaling 153. The Slovin sample formula, the sample in this study amounted to 60 students. The results of this study found that 21.7% of respondents had a very high level of discipline. As many as 20% of respondents have a high level of self-acceptance and 56.7% of respondents have a moderate level of discipline. From the total score obtained of 6811 and divided by 60 students, the result is 113.5 and the value of 113.5 is included in the interval 108-126 or can be categorized as an average of student discipline included in the high category.